Correlation of Intraoperative Findings with Clinical Outcome in Surgical Management of PLID (Bangladesh Journal of Neurosurgery, 2026)
Background: The surgical management of posterior lumbar interbody disc (PLID) remains complex, with  clinical outcomes often varying despite similar intraoperative findings. Understanding this correlation can  enhance surgical strategies and patient recovery. Objective: To assess the correlation between intraoperative  findings and clinical outcomes in the surgical management of PLID, determining predictors of surgical  success. Methods: A prospective cohort study was conducted at the Department of Neurosurgery, Evercare  Hospital Chattogram, between January 2022 and December 2024. A total of 142 patients undergoing PLID  surgery were analyzed. Key intraoperative findings, including the degree of disc herniation, nerve root  compression, and spinal degeneration, were recorded. Clinical outcomes were assessed using the Visual  Analog Scale (VAS) for pain, Oswestry Disability Index (ODI), and the MacNab scale for functional  outcomes. Statistical analysis was performed using SPSS, with Pearson's correlation and independent  t-tests applied. Results: The study revealed a strong correlation between intraoperative findings and clinical  outcomes (p